1996
DOI: 10.1006/viro.1996.0348
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic Variation of SIV: Mutations in V4 Alter the Neutralization Profile

Abstract: Antigenic variation is a characteristic feature of lentiviral infection. The SIV/macaque model of AIDS provides an ideal system in which to investigate the molecular basis of antigenic variation. The purpose of this study was to genetically map the nucleotide changes in env that alter the neutralization phenotype of SIV. Serum taken from an SIVmac239-infected macaque (2D) at 30 weeks postinoculation was found to neutralize the input virus (SIVmac239) and an isolate, P9, obtained at 10 weeks p.i., but did not n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
43
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 4 publications
6
43
0
Order By: Relevance
“…The neutralizing epitope profile of SIV envelope includes the CD4 binding site and gp41 but not the V3 region. There is conflicting evidence as to whether V1, V2, and/or V4 of SIV are targets for antibody neutralization (15,18,19). The present study addresses whether vaccine-induced immune responses accelerate the generation of autologous neutralizing antibodies following SIV challenge in rhesus monkeys and how this humoral immune response can potentially shape viral sequence evolution.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…The neutralizing epitope profile of SIV envelope includes the CD4 binding site and gp41 but not the V3 region. There is conflicting evidence as to whether V1, V2, and/or V4 of SIV are targets for antibody neutralization (15,18,19). The present study addresses whether vaccine-induced immune responses accelerate the generation of autologous neutralizing antibodies following SIV challenge in rhesus monkeys and how this humoral immune response can potentially shape viral sequence evolution.…”
mentioning
confidence: 94%
“…SIV and HIV-1 envelopes share approximately 40% amino acid homology (10,11) and have overlapping variable and constant regions, although the variable region 3 (V3) of HIV-1 envelope does not align with the homologous region of SIV envelope (7). Following SIV infection in rhesus monkeys, SIV envelope evolves most rapidly in variable regions 1 and 4 (V1 and V4, respectively), leading to nucleotide additions, deletions, and/or mutations that can potentially translate to changes in glycosylation (7,9,13,15,19,29,30).…”
mentioning
confidence: 99%
“…Lentiviral antigenic variation is most pronounced in the viral Env proteins that serve as initial primary targets for host immune responses. Studies on the effect of Env variation on antigenic properties indicate that even minor changes in amino acid sequence can dramatically alter antibody and CTL specificities in in vitro assays and immune control of persistent infections in vivo (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Nevertheless, even apparently extensive Env variations may not necessarily cause detectable changes in immune phenotype as measured by in vitro assays alone (18).…”
mentioning
confidence: 99%
“…Fab 201 competed with mouse monoclonal antibodies (KK5 and KK9) that react with a conformation-dependent epitope in the V3 to V4 region (7,21). Previous studies with these mouse monoclonal antibodies have demonstrated that they are highly sensitive to substitutions within the V4 region (25). However, the V123 chimera but not the V4 or the V45 chimera was recognized by IgG1-201, restricting the region of the epitope to the V3 to C3 region.…”
Section: Vol 74 2000mentioning
confidence: 98%
“…However, many of the neutralizing epitopes for SIV have been partially mapped by peptide scanning (20,21) and mutational analysis (3,6,7,25,44). A number of studies conducted with variants of the SIVmac lineage have shown that discrete amino acid substitutions in the envelope glycoprotein can alter the neutralization phenotype (3,25,44). Such changes include the acquisition of novel glycosylation sites as a viral mechanism for avoiding recognition by neutralizing antibody (6).…”
mentioning
confidence: 99%